EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA KELAS X - Riad Hafidzi; Aminuyati Aminuyati; Agus Sugiarto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the effect of video learning on learning outcomes ingeography learning in class X Muhammadiyah Sambas Senior High School. Theresearch method used was the experimental method and the research form QuasiExperimental Design. The population of this study were all class X IIS SMAMuhammadiyah Sambas, totaling 4 classes. The sampling technique was carriedout randomly. Data collection tools in the form of a final test in the form ofobjective questions obtained by an average experimental class of 75.5 and anaverage of the final test of the control class of 70.032 andt count of (2.197) and ttable of (1.670). Based on tcount> ttable means Ha accepted. So, the abovecalculations can be concluded that There are differences in the learning outcomesof class X Muhammadiyah Sambas Senior High School students who useinstructional video media and power point media in the material of geographyresearch steps. Based on the results of the calculation of the effect size, it wasfound that the ES was 0.533. The instructional video media had a moderate effecton the learning outcomes of class X SMA Muhammadiyah Sambas.Keywords: Influence, Learning Outcomes, Learning Video Media